2020
DOI: 10.14198/cuid.2020.58.07
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de enfermeras/os de atención hospitalaria y primaria de salud, sobre el liderazgo de Enfermería

Abstract: Introducción. La legislación chilena atribuye a enfermería la Gestión de Cuidados, implica autonomía, requiriendo enfermeras/os capaces de practicar “liderazgo efectivo” contribuyendo a la óptima salud de la población. Sin embargo, se ha instalado la percepción de que enfermería a nivel nacional ha perdido espacios de opinión y toma de decisiones, lo que hace relevante indagar apreciaciones desde las/os protagonistas respecto al ejercicio de liderazgo en sus prácticas. Material y método. Investigación cualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
3
0
9
Order By: Relevance
“…In such context, the younger Nursing professionals of our training consider that: Nursing workforce that is overcommitted to the institution exerts a negative effect on their self-care. Similarly a study by Lara-Jaque et al that reveals, that new generations of female nurse-leaders see commitment to the institution as a defect, differently from previous generations which consider it as a challenge 16 .…”
Section: /12mentioning
confidence: 86%
See 1 more Smart Citation
“…In such context, the younger Nursing professionals of our training consider that: Nursing workforce that is overcommitted to the institution exerts a negative effect on their self-care. Similarly a study by Lara-Jaque et al that reveals, that new generations of female nurse-leaders see commitment to the institution as a defect, differently from previous generations which consider it as a challenge 16 .…”
Section: /12mentioning
confidence: 86%
“…This dimension imposes tension on three elements that require the right balance, namely: a) the health needs of the population, b) the availability and use of resources in the healthcare systems, and c) the Nursing professionals' vocation or commitment to the care practice. We know that deficient structural conditions, lack of resources and high workload affect care quality, and that authoritarian leaderships exert an impact on the health personnel's commitment and are grounds for conflict in teamwork [16][17] . Our participants associate the resource deficits and the authoritarian styles not only with a reduction in care quality but also with its dehumanization.…”
Section: /12mentioning
confidence: 99%
“…The aforementioned can be considered from the managerial scope as characteristics of the leaders and which are related to their work context. The literature has shown that this type of leadership is related to how companies operate: the starting point is achievement planning by means of numerical goals or objectives, in addition to being recognized as a fundamental cornerstone to which quality care is provided to people is attributed (26). Therefore, the reward becomes the core of transformational leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Revista Uruguaya de Enfermería, 2023;18(1):e2023v18n1a4 DOI: 10.33517/rue2023v18n1a4 -eISSN: 2301-0371 manteniendo un punto de equilibrio en las decisiones compartidas en la atención de las personas y sus familias, siendo un pilar fundamental a lo largo de todo el ciclo vital. Esto se relaciona con un liderazgo avalado en la experiencia laboral, capacitaciones y adquisición de conocimientos, influyendo en la toma de decisiones (31)(32) (33) Y refuerza las ideas planteadas los resultados de Silva y Campos, para quienes el liderazgo contribuye de manera directa y efectiva en el empoderamiento profesional, y realza la importancia de una unidad de GDC. Asimismo, se beneficia el equipo de enfermería con buenos líderes, manteniendo un trabajo en equipo constante y eficiente, basado en valores éticos (34) (35) .…”
Section: Facilitadores Para La Gestión Del Cuidado En Ap: Competencia...unclassified